Performance Analysis of Cone Basin-Based Gravitational Water Vortex Power Plant (GWVPP) by Variations in the Number of Blades - Iim Fatimah; Haswin Dian Fathoni; Bachtera Indarto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2022)
The electricity supply is not evenly distributed for all regions in Indonesia. This is due to the lack of transportation access to reach these areas because of difficult terrain conditions. One of abundant energy sources available in nature is water, which can be used for micro-level power generation. Micro hydro generator usually uses a waterfall with a high head. However, not all of the water flow has a head tall. Therefore, this study proposes a promising prototype of a cone basin-based Gravitational Water Vortex Power Plant (GWVPP). The purpose of this study is to determine the performance of the cone basin-based GWVPP prototype by variation in the number of blades. The vortex turbine is designed with a water flow rate of 169.63 liters/minute and a cone basin with square-shaped blades and variations in the number of blades, namely 2, 4, and 6, with the same turbine blade area of 0.01 m2 . It was found that an increase in the number of blades enhances mechanical characteristics of, e.g. torque and rotational speed, as well as electrical characteristics, e.g. voltage, current, and electric power. The maximum result is achieved when the number of blades is six with the rated power of 5 mW and the rotation speed of 119.351 rpm.